الہامی مذاہب میں غلو فی الدین کے مطالعے میں قرآنی تعلیمات: Quranic Principles Regarding Extremism in Inspirational Religions - Hafiz Saif ur Rehman; Hafiza Sundas Zaman (Al Manhal Research Journal, 2024)
The topic of religious extremism is important in the field of theology, where academics, policymakers, and the general public all have an interest. This article's goal is to analyze religious extremism's tenets and consequences in the context of what the Quran says. Quranic verses explicitly highlight a number of important topics, including justice, fairness, kindness, peace, security, unity, and ethical ideals. These lessons undercut the core of religious extremism, which fuels severe bigotry, fanaticism, and violence among its leaders and adherents. Religious fanaticism gives a misleading understanding of Islamic teachings and distorts the genuine meaning. Islamic teachings often condemn religious fanaticism and promote justice, kindness, peace, security, unity, and other moral values.